Protein Engineering in Industrial Biotechnology - Alberghina, Lilia;Ed (Harwood Academic Publishers, 2000)
Protein engineering has proved to be one of the more fruitful technological approaches in biotechnology, being both very powerful and able to generate valuable intellectual property. The book aims to present examples in which the application of protein engineering has successfully solved problems arising in industrial biotechnology. There is a section on its use to enhance purification of recombinant proteins. The use of protein engineering to modify the activity or the stability of industrial enzymes from lipases to proteases, from carboxypeptidases to glucanases and glucosidases,